1998
DOI: 10.1080/02652039809374723
|View full text |Cite
|
Sign up to set email alerts
|

Validation and use of the CALUX‐bioassay for the determination of dioxins and PCBs in bovine milk

Abstract: There is a strong need for the development of relatively cheap and rapid bioassays for the determination of dioxins and related compounds in food. A newly developed CALUX (Chemical-Activated LUciferase gene eXpression) bioassay was tested for its possible use to determine low levels of dioxins in bovine milk. Data show that this mammalian cell-based test is very sensitive for 2,3,7,8-substituted dioxins and related PCBs, thereby reflecting the relative potencies of these compounds in comparison to TCDD (TEF-va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 30 publications
8
57
1
Order By: Relevance
“…Further, high levels of some PCBs have been shown to antagonize the dioxins if not separated (Garrison et al, 1996). It has been reported that the TEQ value especially in samples containing relatively large amount of PCB 118 might be underestimated in the CALUX bioassay compared to an HRGC/HRMS determination (Bovee et al, 1998;Laier et al, 2003). Inadequate sample clean-up prior to the CALUX bioassay might result in the measurement of activity due to these interfering compounds, and an inaccurate TEQ report for the sample (Brown et al, 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…Further, high levels of some PCBs have been shown to antagonize the dioxins if not separated (Garrison et al, 1996). It has been reported that the TEQ value especially in samples containing relatively large amount of PCB 118 might be underestimated in the CALUX bioassay compared to an HRGC/HRMS determination (Bovee et al, 1998;Laier et al, 2003). Inadequate sample clean-up prior to the CALUX bioassay might result in the measurement of activity due to these interfering compounds, and an inaccurate TEQ report for the sample (Brown et al, 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…Samples of 0.25 g fish oil (kindly supplied by Nutreco, Boxmeer, The Netherlands) were purified on columns containing 10 g acid silica (33% H 2 SO 4 ), as described by Bovee et al [17]. Before total evaporation of the hexane/diethyl ether extract in a SpeedVac, 100 μl dimethyl sulfoxide (DMSO) was added as a keeper.…”
Section: Dr Calux® Screeningmentioning
confidence: 99%
“…The DR CALUX Õ test was carried out as described earlier by Bovee et al (1998). An aliquot of 0.5 g fat was mixed with hexane and extracted on acid silica as described previously.…”
Section: Dr Calux õ Analysismentioning
confidence: 99%